Konsep Pendidikan Islam Holistik Prof. Dr. Tuty Alawiyah serta relevansinya di Era Millenium - Amaliy atul ulya; amaliy atul ulya (Universitas Alma Ata, 2020)
Prof. Dr. Tuty Awawiyah is a female scholar as well as educational thinker who succeded establishing and managing Pesantren-based schools starting form kindergarten, the elementary school, junior high school, the senior high school until the college. The Purpose of this paper is to add insight and treasure about the concept of holistic Islamic education of Prof. Dr. Tuty Alawiyah and its relevance in the Millenium Era. Based on reseach and literature review that have been done, Islamic holistic education can be interpreted as education that is able to answer the problems of education faced in the word of education di the millennium era, for Islamic holistic education is education that shapes something in a whole way, therefore it becomes a very large unity that any other exithing combination. In can be concluded that, some holictic Islamic Education concept form Prof. Dr Tuty Alawiyah are very relevant so it needs to be discussed and they will appropriate as a quide in the millennium Era. Keyword: Tuty Alawiyah, Education, Millennium Era.